First description of male from parthenogenesis in a chironomid species Paratanytarsus grimmii (Schneider, 1885) (Diptera: Chironomidae) - Kodama, Atsuya; Saito, Hidetoshi; Kawai, Koichiro (Zootaxa, 2025)
Paratanytarsus grimmii (Schneider, 1885) is a parthenogenetic species of the family Chironomidae and a pest of water supply systems. This is an apomictic, parthenogenetic species that lacks males. Adult males of P. grimmii have not been known in previous studies, however have been described for the first time based on specimens reared from eggs in the laboratory and confirmed by DNA sequencing. The male of P. grimmii is closely related to those of P. laetipes (Zetterstedt, 1850) and P. toyaprimus Sasa, 1988 owing to shared morphological features of the hypopygium.